Early evolution stage of AGN. Issue Volume 10:Issue S313(2014) (24th March 2015) - Kunert-Bajraszewska, M.; Labiano, A.; Siemiginowska, A.; Guainazzi, M.; Gawroński, M.
Abstract: Radio sources are divided into two distinct morphological groups of objects: Fanaroff-Riley type I and type II sources. There is a relatively sharp luminosity boundary between these at low frequency. The nature of the FR division is still an open issue, as are the details of the evolutionary process in which younger and smaller GHz-peaked spectrum (GPS) and compact steep spectrum (CSS) sources become large-scale radio structures. It is still unclear whether FRII objects evolve to become FRIs, or whether a division has already occurred amongst CSS sources and some of these then become FRIs and some FRIIs. We explored evolution scenarios of AGNs using new radio, optical and X-ray data of unstudied so far Low Luminosity Compact (LLC) sources. We suggest that the determining factors of the further evolution of compact radio objects could occur at subgalactic (or even nuclear) scales, or they could be related to the radio jet - interstellar medium (ISM) interactions and evolution. Our studies show that the evolutionary track could be related to the interaction, strength of the radio source and excitation levels of the ionized gas instead of the radio morphology of the young radio source.